1991
DOI: 10.1071/wr9910547
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal movements of grey-headed flying-foxes, Pteropus poliocephalus (Chiroptera : Pteropodidae), from two maternity camps in northern New South Wales

Abstract: Seasonal movements of 22 Pteropus poliocephalus, from two maternity camps in north-eastern New South Wales, were monitored from January to June 1989 using radiotelemetry. The animals moved independently in time and space among various communal roosts located 8-610 km from the maternity camp sites. Generally, P. poliocephalus from a camp near rainforest (Currie Park, Lismore) remained within 50 km of the maternity site. These localised movements were attributed to the continued availability of fruits in the rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
189
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(201 citation statements)
references
References 2 publications
12
189
0
Order By: Relevance
“…Host aggregation during reproduction [23,30,48,49] or periods of resource concentration [15,22] are other potential drivers of transmission that need further investigation. Finally, environmental stress could drive geographical 'stress synchrony'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Host aggregation during reproduction [23,30,48,49] or periods of resource concentration [15,22] are other potential drivers of transmission that need further investigation. Finally, environmental stress could drive geographical 'stress synchrony'.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative assessments of long-term changes to flying fox populations were obtained by comparing historic literature [48][49][50] to current assessments [26][27][28][29]31] and expert opinion. Connectivity estimates from radio and satellite telemetry studies of P. poliocephalus [15,36] and radio telemetry studies of P. alecto [51,52] differed substantially, hence, we explored HeV dynamics over the entire range of the connectivity parameter, c, for which simulations persisted (see the electronic supplementary material, methods).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here on present-day regional-scale genetic structure in the spectacled flying fox (Pteropus conspicillatus), generally assumed to be a rainforest specialist, and on the insights modern-day processes may provide for understanding responses of an extremely mobile animal to Pleistocene habitat contraction and fragmentation. All flying foxes are potentially extremely mobile and some species make seasonal migrations across hundreds of kilometres, following cycles of fruiting and flowering of favoured food trees (Eby 1991;Tidemann and Nelson 2004). Species such as the little red flying fox (Pteropus scapulatus) and grey-headed flying fox (P. poliocephalus) traverse many hundreds of kilometres in the course of a year and are apparently panmictic (Sinclair et al 1996;Tidemann 1996: Luly et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance for NiV in pre-border regions close to Australia has been limited to date, so the prevalence in these regions is unknown. However, flying-foxes can fly considerable distances (Eby, 1991;Vardon et al, 2001;Tidemann and Nelson, 2004), such as between peninsular Malaysia and Sumatra and between Papua New Guinea and Queensland (Breed et al 2010). There also appears to be a reasonable level of connectivity between bats in preborder regions since genetic studies of Pteropus vampyrus have shown high levels of gene flow between populations in Indonesia, Malaysia and East Timor .…”
Section: Risk Assessmentmentioning
confidence: 99%